Ultra-small yellow defective TiO2 nanoparticles for co-catalyst free photocatalytic hydrogen production. (June 2016) - Wu, Qingping; Huang, Feng; Zhao, Mingshi; Xu, Ju; Zhou, Jiangcong; Wang, Yuansheng
Abstract: Blue TiO2 (Ti 3+ defected TiO2 ) nanoparticles have been intensively investigated for photocatalytic H2 production. However, the Ti 3+, with energy level 1.0 eV below the conduction band, cannot initiate visible light driven H2 production. Thus, Pt or NiOx is often used as a co-catalyst, which is economically unattractive and environmentally contaminative. In this paper, the ultra-small yellow TiO2 nanoparticles ( 3 nm) have been firstly synthesized without introducing any external dopants. The titanium vacancies (acceptor) and titanium interstitials (donor) that incorporated in the yellow TiO2 are evidenced by various characterization techniques, and their formation mechanism is proposed. Photocatalytic evaluations indicate that the acceptor–donor defects play key roles in the catalytic process, not only initiating, but also promoting the visible light driven H2 production. The improved activity is also evidenced by that the simulated solar light driven H2 production for the yellow TiO2 is 3.7 fold comparing to that of the normal TiO2 . A reasonable explanation is that the acceptor-donor defect associates form internal polarization for spontaneously separating photo-generated charge-carriers. The improved charge-carrier separation has been confirmed by photoluminescence spectra and photoluminescence emission decay profiles. Instead of the traditional TiO2 based photocatalysts, the acceptor–donor defect engineered photocatalyst system offers a new approach for simultaneously initiating and promoting visible light driven co-catalyst free H2 production. Graphical abstract: Highlights: The ultra-small yellow TiO2 nanoparticles were firstly synthesized. The intrinsic defects in the yellow TiO2 initiate and promote the visible light H2 production. The defects in the yellow TiO2 also greatly enhance the solar light driven H2 production. The defects in the yellow TiO2 improve the charge-carrier separation. The improved charge-carrier separation could be due to the internal polarization.